GROWTH AND PRODUCTION RESPONSE OF PAKCOY (BRASSICA RAPA L.) ON DIFFERENT CONCENTRATIONS OF ECO ENZYME APPLICATIONS UNDER AQUAPONIC SYSTEM - Ulfah, Maria; Hasanah, Imroatul; Hayat, M. Syaipul; Dewi, Endah Rita Sulistya (International Journal of Research -GRANTHAALAYAH, 2025)
Pakcoy (Brassica rappa L) is one of the most popular vegetable commodities, but the growth and production of this plant cannot meet the demand. The purpose of this study was to determine the effect of giving eco enzyme in aquaponics system on the growth and production of Pakcoy. This research was conducted in Patemon, Gunung Pati, Central Java, Indonesia. The method used is a 3x3 Completely Randomized Design (CRD). The treatments used were: P0 (control), P1 (addition of eco enzyme 1 mL/1 L water), P2 (addition of eco enzyme 1.5 mL/1 L water). Parameters observed were leaf length, leaf width, number of leaves, and plant wet weight. Data analysis used ANOVA by comparing Fcount with Ftable at the 5% level. The results showed that the treatment with eco-enzyme affected the growth and production of Pakcoy in the addition of length (20.17 cm), width (10.16 cm), number of leaves (24 strands) and plant wet weight (225.66 grams). The results of this study can be concluded that the application of eco-enzyme in aquaponics system affects the growth and production of Pakcoy. Excessive use of eco-enzyme will cause stunted plant growth due to acidic pH conditions.